(3GdMeGjI GdJTQjYjI h GdbVGFjI dMb GdgLQI h MQjI GdJfbd (B: s (3OQGSI ebGQfI (B/ s - (3QHGH TcQi eMeO eMehOs; (3UHQi eMeO GdSfhSi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JfGhdfG MQjJjf geG eMd GgJeGe LehY GdHTQ GdG h geG MQjJG GdJfbd h GdgLQI(B. (3GTJed GdHGH GdChd Ydi GdMeGjI GdJTQjYjI dMb GdgLQI h MQjI GdJfbd(B. (3h ajg JWQbfG Gdi GdJfXje GdJTQjYi dMb GdgLQI h MQjI GdJfbd ai cdG ef GdGSdGe h GdOSGJjQ GdeUQjI GdeJYGajI(B. (3h cPdc Mb GdgLQI h MQjI GdJfbd ai GdJTQjY GdaQfSi(B. (3ceG PcQfG GdbjhO GdJi JQO Ydi Mb GdgLQI h MQjI GdJfbd h efgG GdefY ef GdSaQ(B. (3ceG JVefJ Jdc GdbjhO bQGQGJ GdGYJbGd ai Xd GdXQha GdSjGSjI(B. (3h cPdc GdbjhO GdJi JQO Ydi ONhd h GbGeI GdCLGfH(B. (3h JVef GdHGH GdKGfi GdMeGjI GdbVGFjI dMb GdgLQI h MQjI GdJfbd h GdPi JfGhdfG ajg GdQbGHI GdbVGFjI Ydi GdbQGQGJ GdeJYdbI HMb GdgLQI h MQjI GdJfbd(B. (3ai VhA GdeHGOi GdJi GbQgG eLdS GdOhdI GdeUQi(B. (3h Jdc GdJi GbQgG eLdS GdOhdI GdaQfSis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B465-473s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdMeGjI GdJTQjYjI s; (3GdMeGjI GdbVGFjI s; (3GdgLQI s; (3Mb GdgLQI hMQjI GdJfbd aj GdJTQjY GdaQfSjs; (3GdefY ef GdSaQs; (3GdefY ef eZGOQI GdHdGO aj GdJTQjY GdaQfSjs; (3GdGYJbGds; (3bQGQGJ GHYGO GdGLGfHs; (3GdGbJjGO ddMOhOs; (3JQMjd GdGLGfH aj eUQs; (3GdMeGjI GdbVGFjI dMb GdgLQI hMQjI GdJfbds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes